I-TEACH MODEL IN INCLUSION CLASSROOM FOR ECCE TEACHERS (Application of Learning Model for Children with Special Needs in Regular Classes) - Putri Sari Ulfa Sembiring; Dewi Sartika Panggabean; Zulvia Misykah (Sean Institute, 2022)
Inclusive education is narrowly defined or based on the assumption of 'children as a problem and if then the definition is used to develop or monitor its practice, then inclusive education will fail and not be sustainable. However, the fact found is that there are still students with special needs who are always in special classes during school hours and do not study in the classroom with non-special needs children. The model can have a negative impact on students with special needs, according to Dunn (1968) in Smith (2012) emphasizing that labeling children to be placed in special classes creates a very destructive stigma to their self-concept, and the transfer of children from regular classes to special classes may have a significant influence on feelings of inferiority and self-acceptance problems. The purpose of this research study is to be able to determine the results of the achievement of inclusion learning methods in children with special needs in the regular classroom. In the model book I-teach (inclusive teaching) for PAUD teachers, it is said that there is a learning drive that has a positive response to children with special needs when combined with normal children, but is accompanied by principals, accompanying teachers, psychology and special doctors in achieving the development of the motor system and child growth. This research is a qualitative research, in compiling and analyzing data and only using reading materials or commonly referred to as library research. Based on the results of the research analysis above, it can be concluded that this I-teach model provides an overview of the framework for developing, implementing and preparing teachers to teach in inclusion classes. The inclusion teaching model outlines a teaching process that requires collaboration to prepare teaching for teachers in the inclusion classroom. The inclusive teaching model is a teaching model intended for teachers who teach in inclusion classes, where the learning process involves the presence and participation of children with special needs. Inclusive teaching cannot stand alone a model that is independent, but rather the involvement of various parties that aims to provide educational services and is appropriate for every child including children with special needs in it.